EFFICIENT REFORM OF HIGHER PROFESSIONAL EDUCATION (HPE) WITHIN PUBLIC ADMINISTRATION DIMENSION - M A Ignatskaya (RUDN Journal of Public Administration, 2014)
The article deals with the efficiency related management problems of HPE reforming processes within Public Administration sphere. Models for modernization through educational context along with managing staff potential through ensuring efficiency within PA are highlighted. The view on the above problems of aggregated employer in contemporary Russia is analyzed as well as the view of HPE institutions.